Estate Planning - Martie Gillen; Josephine Turner; Vervil Mitchell (EDIS)
Estate planning has to do with living, not just with decisions about who inherits property. An estate plan is a pattern, a guide, or a master method for working toward financial security and the family’s future welfare. To be most effective, estate planning should involve all members of the family. The objectives of estate planning will differ among families because of varying circumstances, such as differences in assets, value judgments, personal desires, and number of children. Consider these purposes for estate planning. This revised 7-page fact sheet was written by Martie Gillen, Josephine Turner, and Vervil Mitchell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.